Blue Ocean Shift: Evidence-Based Practice in the Professional Development of Teachers - Nelson, Jenna; Bohanon, Hank (International Journal of Advanced Corporate Learning (iJAC), 2019)
With the implementation of the Every Student Succeeds Act (ESSA) in the United States, teachers have been given new responsibilities tied to supporting student scholastic and behavioral needs. The recent implementation of ESSA has left educators with minimal professional development support options to acquire skills to support students under this Act. To meet the diverse professional needs of teachers, it is necessary to look toward new cost-effective methods for professional development that stretch beyond in-person trainings, and that will prepare teachers to support the scholastic and behavioral needs of all learners. The authors propose incorporating the Blue Ocean Shift (BOS) strategy to identify alternative methods for teacher development. BOS comes from the business setting and is a strategy used in market development. The authors apply BOS to education through exposing its applicability as an assessment process. This assessment process can support the identification and development of online teaching tools for supporting multi-tiered systems of supports (MTSS) coaches in their training of teachers for school improvement efforts. The authors analyze the current professional development options provided to teachers and evaluate the use of BOS to determine innovative practices that MTSS coaches can implement to develop teacher skills and promote student learning.